New Zealand Yearbook of International Law : Volume 20, 2022 - Jefferson, David J.; Riffel, Christian (International Law E-Books Online, Collection 2024., 2024)
The New Zealand Yearbook of International Law is an annual, internationally refereed publication whose purpose is to provide a yearly reference for legal materials and critical commentary on issues of international law. The Yearbook also serves as a valuable tool to identify trends, state practice, and policies in the development of international law in New Zealand, the Pacific region, the Southern Ocean, and Antarctica, and to generate scholarship in those fields. In addition to presenting peer-reviewed legal research, the Yearbook contains an annual 'Year-in-Review' that covers developments in international law of particular interest to New Zealand, and a dedicated section on the South Pacific. This Yearbook covers the period 1 January 2022 to 31 December 2022.